Anatomy of three Onosma species from Turkey - Akcin, Oznur Ergen; Binzet, Riza (Bangladesh Journal of Botany, 2019)
Three Onosma L. species (O. papillosa Riedl, O. rutila Hub-Mor. and O. auriculata Aucher ex DC.) were examined anatomically. All these taxa had secondary root structure and xylem which were composed of sclerenchymatic cells and tracheary elements. O. papillosa has crystals and sclereids in the stem and leaf. Sand crystals are seen in the pith region of O. auriculata. O. papillosa and O. auriculata has bifacial leaf types and O. rutila has equifacial type. Stomata are anisocytic, anomocytic and staurocytic. These species have long and short simple eglandular and glandular trichomes. Setae with glabrous tubercles are present in O. papillosa and O. rutila. O. auriculata has porrect-stellate trichomes. Simple trichomes are unicellular and generally short. They have lignified, ornamental or smooth walls.